Response of Growth and Production of Soybean Varieties Edamame ( Glycine max L. Meriil) To Super Compost Fertilizer and POC JST - Ade Fipriani Lubis; Turi Handayani; Vanny Erlangga (Kirana Publisher (KNPub), 2022)
This research was conducted at the Experimental Field of the Faculty of Agriculture, Asahan University (UNA) Kisaran, Asahan Regency, North Sumatra, in February - April 2022. This study was arranged based on a factorial randomized block design (RBD) with 2 treatment factors and 3 replications. The first factor was the treatment of super compost (K) with 3 levels, namely K0 = 0 tons/ha (control), K1 = 5 tons/ha (0.94 kg/plot), K2 = 10 tons/ha (1 .88 kg/plot). Rhizobium Biological Fertilizer per 250 g of soybean seeds. The second factor is the concentration of JST POC (J) with 4 levels, namely J 0 = 0 ml/litre of water/plot, J 1 = 15 ml/litre of water/plot (1.5%), J 2 = 30 ml/litre of water/ plot (3%), J 3 = 45 ml/litre of water/plot (4.5%). The results showed that the treatment of compost had a significant effect on the concentration of POC ANN (J), which significantly affected the height of plants 3 weeks after transplanting, the number of branches 3 weeks after transplanting, the number of filled pods per sample plant, pod production per sample, and pod production per plot. The best plant height 3 weeks after transplanting at a dose of 1.88 kg of super compost (K 2 ) is 30.73 cm, the number of branches aged 3 weeks after transplanting is best at a dose of 1.88 kg of super compost (K 2 ), i.e. 8.40 branches, the best number of filled pods per sample plant at a dose of 1.88 kg of super compost (K 2 ) is 50.53 pods, the best pod production per sample is at a dose of 1.88 kg of super compost (K 2 ) i.e. 31.43 g, the best product per plot at the dose of super compost (K 2 ) is 0.30 kg. POC ANN concentration treatment (J) significantly affected plant height 3 weeks after transplanting, number of branches aged 3 weeks after transplanting, number of filled pods per sample plant, pod production per sample, and pod production per plot. The best plant height at 3 weeks after transplanting with POC ANN treatment with a concentration of 4.5% (J 3 ) is 29.23 cm, and the best number of branches aged 3 weeks after transplanting is best with POC ANN treatment with a concentration of 4.5% (J 3 ) namely 7.81 branches, the best number of filled pods per sample plant with POC ANN concentration of 4.5% (J 3 ), namely 48.76 pods, the best pod production per sample with POC ANN treatment of 4.5% (J 3 ) namely 29.89 g and the best production per plot with POC ANN treatment with a concentration of 4.5% (J 3 ) is 0.31 kg. The interaction of super compost fertilizer and POC ANN concentrations did not affect all parameters of the edamame soybean variety